Establishing local manufacture of PPE for healthcare workers in the time of a global pandemic - Anastasia Nilasaroya; Alan Matthew Kop; Ryan Christopher Collier; Brendan Kennedy; Lachlan James Kelsey; Faz Pollard; Jennifer Fong Ha; David Anthony Morrison (Heliyon, 2023)
A face shield is a secondary personal protective equipment (PPE) for healthcare workers (HCW). Worn with the appropriate face masks/respirators, it provides short term barrier protection against potentially infectious droplet particles. Coronavirus disease 2019 (COVID-19) caused a spike in demand for PPE, leading to a shortage and risking the safety of HCW. Transport restrictions further challenged the existing PPE supply chain which has been reliant on overseas-based manufacturers. Despite the urgency in demand, PPE must be properly tested for functionality and quality. We describe the establishment of local face shields manufacture in Western Australia to ensure adequate PPE for HCW. Ten thousand face shields for general use (standard) and for ear, nose and throat (ENT) specialist use were produced. Materials and design considerations are described, and the face shields were vigorously tested to the relevant Standards to ensure their effectiveness as a protective barrier, including splash and impact resistance. Comparative testing with traditional and other novel face shields was also undertaken. Therapeutic Goods Administration (TGA) licence was obtained to manufacture and supply the face shields as a Class I medical device. The swiftness of process is a credit to collaboration from industry, academia and healthcare.